2021
DOI: 10.1088/1755-1315/733/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the sweetness level of avomango (Gadung Klonal 21) using multi-predictor local polynomial regression

Abstract: One of the mango’s maturity aspects is the sweetness of the fruits. Mature Avomango has a high degree of sweetness, characterized by a high total soluble solids (TSS) content. Currently, many non-destructive tests are using Near Infra-Red (NIR) spectroscopy to find out the TSS content. NIR spectroscopy generates spectra data, which can be used as predictors to predict Avomangos sweetness level. This study aims to predict the level of Avomangos sweetness by using a multi-predictor local polynomial regression ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…All treatment spectra revealed that the best predictive model used MLPR, with the highest R 2 value and the lowest RMSE, MSE, and MAPE values compared with the other regression methods. This is consistent with the results of the previous studies by Ulya et al 16,26 The order of prediction performance based on the regression method from the best is MLPR, SVMR and KPLSR. MLPR is a novel method for predicting the internal quality of fruits developed by Ulya et al 16,26 This study confirms that the MLPR method can produce a robust predictive model for determining the internal quality of mangoes; MLPR (nonparametric regression) has predictive performance with a lower MAPE value than that of the MPR (parametric regression).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…All treatment spectra revealed that the best predictive model used MLPR, with the highest R 2 value and the lowest RMSE, MSE, and MAPE values compared with the other regression methods. This is consistent with the results of the previous studies by Ulya et al 16,26 The order of prediction performance based on the regression method from the best is MLPR, SVMR and KPLSR. MLPR is a novel method for predicting the internal quality of fruits developed by Ulya et al 16,26 This study confirms that the MLPR method can produce a robust predictive model for determining the internal quality of mangoes; MLPR (nonparametric regression) has predictive performance with a lower MAPE value than that of the MPR (parametric regression).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of the previous studies by Ulya et al 16,26 The order of prediction performance based on the regression method from the best is MLPR, SVMR and KPLSR. MLPR is a novel method for predicting the internal quality of fruits developed by Ulya et al 16,26 This study confirms that the MLPR method can produce a robust predictive model for determining the internal quality of mangoes; MLPR (nonparametric regression) has predictive performance with a lower MAPE value than that of the MPR (parametric regression). Table 2 proves that SVMR outperforms KPLSR with higher R 2 values, lower MSE, RMSE and MAPE.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations